Odpowiedzi

2009-10-07T23:02:24+02:00
A)lnx+3=ln(x+1) zał:x>0 i x>-1 czyli x>0
lnx+lne³=ln(x+1)
lnx*e³=ln(x+1)
x*e³=(x+1)
x*e³-x=1
x(e³-1)=1
x=1/(e³-1)
b)log ⅓ (5-x)≥-2 zał:5-x>0→→x<5
log ⅓ (5-x)≥log ⅓ (⅓)⁻² malejąca
(5-x)≤ (⅓)⁻²
5-x≤9
x≥-4 i zał
czyli x∈<-4,5)

a)lnx+2=ln(x+2) zał:x>0 i x>-2 →→→x>0
lnx+ln e²=ln(x+2)
lnx* e²=ln(x+2)
x* e²=(x+2)
x* e²-x=2
x( e²-1)=2
x=2/( e²-1)

b)log½ (x-2)≥-2 zał:x>2
log½ (x-2)≥log½ (½)⁻² malejąca
(x-2)≤ (½)⁻²
x-2≤4
x≤6 i zał
x∈(2,6>
2009-10-07T23:17:36+02:00
A)lnx+3=ln(x+1)
oraz zał:x>0 i x>-1
czyli x>0
lnx+lne³=ln(x+1)
lnx*e³=ln(x+1)
x*e³=(x+1)
x*e³-x=1
x(e³-1)=1
x=1/(e³-1)∈D
b)log ⅓ (5-x)≥-2
zał:5-x>0
x<5
log ⅓ (5-x)≥log ⅓ (⅓)⁻² f.malejąca zmiana znaku nierownosci
(5-x)≤ (⅓)⁻²
5-x≤9
x≥-4 i załx<5
czyli x∈<-4,5)

a)lnx+2=ln(x+2)
zał:x>0 i x>-2
mamy
x>0
lnx+ln e²=ln(x+2)
lnx* e²=ln(x+2)
x* e²=(x+2)
x* e²-x=2
x( e²-1)=2
x=2/( e²-1)∈D

b)log½ (x-2)≥-2
zał:x>2
log½ (x-2)≥log½ (½)⁻² f.malejąca
(x-2)≤ (½)⁻²
x-2≤4
x≤6 i zał x>2
x∈(2,6>
1 1 1